Implementasi Etika Bisnis dan Dampaknya Bagi Keberlanjutan Bisnis ada Perusahaan - Hamqur Abdillah, Jinan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this study is to determine the implementation of business ethics in business enterprises. This research uses literature research methods based on expert opinions regarding business processes and practices in the company. This type of business method can be used in any situation. Establishing mutual trust in establishing partnerships, both micro and macro, can have a significant impact on the company's reputation. Of course, this does not bring immediate benefits, but is a kind of long-term investment for various aspects of the business field. Business ethics are needed by companies which will have an impact on the sustainability of the business run by the company.